Community-acquired Invasive Bacterial Disease in Urban Gambia, 2005–2015: A Hospital-based Surveillance. (30th August 2019) - Darboe, Saffiatou; Okomo, Uduak; Muhammad, Abdul-Khalie; Ceesay, Buntung; Jallow, Mamadou; Usuf, Effua; Tweed, Sam; Akpalu, Edem; Kwambana-Adams, Brenda; Kariuki, Samuel; Antonio, Martin; Bradbury, Richard S; et al.
Abstract: Background. Invasive bacterial diseases cause significant disease and death in sub-Saharan Africa. Several are vaccine preventable, although the impact of new vaccines and vaccine policies on disease patterns in these communities is poorly understood owing to limited surveillance data. Methods. We conducted a hospital-based surveillance of invasive bacterial diseases in The Gambia where blood and cerebrospinal fluid (CSF) samples of hospitalized participants were processed. Three surveillance periods were defined in relation to the introduction of pneumococcal conjugate vaccines (PCVs), before (2005- 2009), during (2010–2011) and after (2012–2015) PCV introduction. We determined the prevalences of commonly isolated bacteria and compared them between the different surveillance periods. Results. A total of 14 715 blood and 1103 CSF samples were collected over 11 years; overall, 1045 clinically significant organisms were isolated from 957 patients (972 organisms [6.6%] from blood and 73 [6.6%] from CSF). The most common blood culture isolates were Streptococcus pneumoniae (24.9%), Staphylococcus aureus (22.0%), Escherichia coli (10.9% ), and nontyphoidal Salmonella (10.0%). Between the pre-PCV and post-PCV eras, the prevalence of S. pneumoniae bacteremia dropped across all age groups (from 32.4% to 16.5%; odds ratio, 0.41; 95% confidence interval, .29–.58) while S. aureus increased in prevalence, becoming the most prevalent bacteria (from 16.9% to 27.2%; 1.75; 1.26–2.44). Overall, S. pneumoniae (53.4%), Neisseria meningitidis (13.7%), and Haemophilus influenzae (12.3%) were the predominant isolates from CSF. Antimicrobial resistance to common antibiotics was low. Conclusions. Our findings demonstrate that surveillance data on the predominant pathogens associated with invasive disease is necessary to inform vaccine priorities and appropriate management of patients. Abstract : The etiology of invasive bacterial disease has changed since the introduction of routine pneumococcal vaccines. Staphylococcus aureus has emerged as the leading cause of bacteremia.